Innovation games creating breakthrough products through collaborative play - Hohmann, Luke (Addison-Wesley, 2006)
Innovation Through Understanding sm The toughest part of innovation? Accurately predicting what customers want, need, and will pay for . Even if you ask them, they often can't explain what they want. Now, there's a breakthrough solution: Innovation Games . Drawing on his software product strategy and product management consulting experience, Luke Hohmann has created twelve games that help you uncover your customers' true, hidden needs and desires. You'll learn what each game will accomplish, why it works, and how to play it with customers. Then, Hohmann shows how to integrate the results into your product development processes, helping you focus your efforts, reduce your costs, accelerate time to market, and deliver the right solutions, right from the start . Learn how your customers define success Discover what customers don't like about your offerings Uncover unspoken needs and breakthrough opportunities Understand where your offerings fit into your customers' operations Clarify exactly how and when customers will use your product or service Deliver the right new features, and make better strategy decisions Increase empathy for the customers' experience within your organization Improve the effectiveness of the sales and service organizations Identify your most effective marketing messages and sellable features Innovation Games will be indispensable for anyone who wants to drive more successful, customer-focused product development: product and R&D managers, CTOs and development leaders, marketers, and senior business executives alike.
Print version record
Keywords: New products; Production management; Games; Production; Gestion; gestion de la production; innovation